Persepsi Guru terhadap Penggunaan Media Pembelajaran Berbasis Digital di SDIT Ridhotullah - Nia Hartati; Rini Aulida; Sartono Sartono (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The purpose of this study was to examine how elementary school teachers perceive the use of digital learning resources in their lesson plans. Digital technology has many potentials to enhance students’ learning ability and engagement. This study combined case study methodology with qualitative approach. Interviews with several elementary school teachers were used to collect data. The results of the study showed that teachers have different opinions about digital learning resources. To deliver materials, increase students’ enthusiasm for learning, and provide a variety of learning materials, some educators viewed digital media as an interesting and successful medium. They also understood how important it is to incorporate technology into the current curriculum. However, other teachers expressed concerns about inadequate infrastructure as well. This study underlines the need for ongoing assistance in the form of instruction, provision of sufficient resources, and creation of a successful plan to integrate digital learning materials in elementary schools.